PENINGKATAN HASIL BELAJAR PESERTA DIDIK MENGGUNAKAN MODEL DISCOVERY LEARNING PADA PEMBELAJARAN PENDIDIKAN PANCASILA DI KELAS V SEKOLAH DASAR - Ilham Muarif; Atri Waldi; Yesi Anita; Serly Safitri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe the planning, implementation, and improvement of student learning outcomes in Pancasila Education through the application of the Discovery Learning model in class V of SDN 16 Puncak Lawang, Agam Regency. This research was motivated by the low learning outcomes of students, where only 35% of students reached the Learning Objective Achievement Criteria (KKTP) with a class average of 69.8, caused by teacher-centered learning and limited student engagement in constructing their own understanding of Pancasila values. This study used a Classroom Action Research (CAR) design referring to the Kemmis and Mc Taggart model, consisting of planning, action, observation, and reflection, carried out in two cycles: Cycle I (two meetings) and Cycle II (one meeting). The subjects were the class teacher and 20 fifth-grade students. Data were collected through observation, test, and non-test techniques, then analyzed descriptively and quantitatively. The results showed that the quality of the lesson plan increased from an average of 82.14% (Good) in Cycle I to 92.85% (Very Good) in Cycle II; teacher activity increased from 87.5% to 96.8%; and student activity increased from 76.75% to 92.8%. Student learning outcomes also improved: the attitude aspect increased from 72.08 to 86.67, the knowledge aspect from 76 to 88, and the skill aspect from 75.63 to 93.13, with all students reaching the KKTP score of 75 by the end of Cycle II. It can be concluded that the application of the Discovery Learning model effectively improves student learning outcomes in Pancasila Education.